Pengaruh berbagai konsentrasi pupuk organik cair berbahan dasar tangkos kelapa sawit terhadap pertumbuhan semai pala (Myristica fragrans Houtt) di lapangan - Gafar, Abd.; Muslimin; Taiyeb, Asgar; Yusran; Wulandari, Retno; Megawati, Kartika (Jurnal Bisnis Kehutanan dan Lingkungan, 2024)
This research was carried out for two months, from July to September 2023 located at the Arboretum of the Faculty of Forestry, Tadulako University, Palu, Central Sulawesi. This study used the Complete Randomized Design (RAL) method, consisting of Five Treatments M0 = Soil Without POC (control), M1 = Concentration 45% (450ml POC + 550ml water), M2 = Concentration 50% (500ml POC + 500ml water), M3 = Concentration 55% (550ml POC + 450ml water), M4 = Concentration 60% (600ml POC + 400ml water) Of the five treatments repeated 6 times each, so that a total of thirty (30) treatment samples were used. The parameters observed in this study were the increase in seedling height, the increase in the number of leaves, and the increase in stem diameter. The research data was analyzed using fingerprint analysis. Further tests were carried out using the Real Difference Test (BNJ) at the level of 5%. The results of fingerprint analysis show that the application of various concentrations of liquid organic fertilizer made from oil palm tangkos has a significant effect on the increase in seedling height, number of leaves, and stem diameter in the field. The 55% concentration treatment (M3) gave the best effect with an average height increase of 8.25cm, an increase in the number of leaves by 2.5 strands and an increase in stem diameter by 1.81mm.